THE ROLE OF TAXES IN STIMULATING NATIONAL INFRASTRUCTURE DEVELOPMENT - Pasalbessy, Victor F. (MSJ : Majority Science Journal, 2025)
This study aims to analyze the role of tax as the main source of financing national infrastructure development in Indonesia. Infrastructure has a vital role in driving economic growth, improving connectivity, and supporting public services. The research method used is a qualitative-descriptive approach with literature study as the main data collection technique. Data sources come from government reports, tax regulations, and scientific publications related to fiscal policy and infrastructure development. The results show that taxes, particularly income tax and value-added tax, contribute significantly to the State Budget (APBN) which is the basis for funding infrastructure projects. The government also utilizes fiscal policy instruments, such as tax incentives and earmarking, to support national strategic projects. Nonetheless, challenges in optimizing tax revenue such as taxpayer compliance and tax base broadening remain obstacles that need to be resolved in order for infrastructure development to be sustainable. This study concludes that improving the effectiveness of the tax system is crucial in strengthening the country's fiscal capacity to fund national infrastructure development in a sustainable manner.